2015
DOI: 10.1109/tii.2015.2485520
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Multiobjective Evolutionary Algorithm Based on Decomposition for Solving the Unit Commitment Problem

Abstract: In this paper, a multi-objective evolutionary algorithm based on decomposition (MOEA/D) is proposed to solve the unit commitment (UC) problem as a multi-objective optimization problem considering minimizing cost and emission as the multiple objectives. Since, UC problem is a mixed-integer optimization problem, a hybrid strategy is integrated within the framework of MOEA/D such that genetic algorithm (GA) evolves the binary variables while differential evolution (DE) evolves the continuous variables. Further, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Two overtaking mission scenarios are firstly constructed for the purpose of comparison: Firstly, comparative studies were performed between the proposed FAMOPSO and other state-of-the-art evolutionary multiobjective optimization (EMO) methods. For example, a modified NSGA-II (MNSGA-II) algorithm proposed in [31], an enhanced MOEA/D-DE method investigated in [32], and an improved multiobjective artificial bee colony (I-MOABC) developed in [20]. Different from the traditional NSGA-II algorithm, a well-distributed set of reference point and a new diversity factor were adopted in the MNSGA-II method in order to avoid the premature convergence.…”
Section: Comparison Against Other Optimization Methodsmentioning
confidence: 99%
“…Two overtaking mission scenarios are firstly constructed for the purpose of comparison: Firstly, comparative studies were performed between the proposed FAMOPSO and other state-of-the-art evolutionary multiobjective optimization (EMO) methods. For example, a modified NSGA-II (MNSGA-II) algorithm proposed in [31], an enhanced MOEA/D-DE method investigated in [32], and an improved multiobjective artificial bee colony (I-MOABC) developed in [20]. Different from the traditional NSGA-II algorithm, a well-distributed set of reference point and a new diversity factor were adopted in the MNSGA-II method in order to avoid the premature convergence.…”
Section: Comparison Against Other Optimization Methodsmentioning
confidence: 99%
“…The objective function of UC as a well-known problem in power system operation is commonly modeled as (1a) which includes the energy production costs presented in (1b) and start-up/shut-down costs provided in (1c) and (1d) [2]- [6], [13], [16]. …”
Section: A Operational Cost Objective Functionmentioning
confidence: 99%
“…System operator needs to have sufficient up-anddown SR to properly manage power systems' uncertainties and contingencies. To the best of our knowledge, the previous works in the area of unit commitment (UC) are related to solution methodologies for UC [2]- [6], risk-constrained UC and modeling related uncertainties [6]- [9], and scheduling of sufficient reserve [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-objective version of the UCP has not been the subject of extensive research and most of the works reported in the literature either considers the emissions as constraints [4,5] or transforms the problem into a single objective one, see, e.g., [6][7][8]. A recent review on the use of multi-objective optimization (MOO) in the energy sector, namely in the electricity sector, can be found in [9].…”
Section: Introductionmentioning
confidence: 99%